ANALISIS RASIO PROFITABILITAS DALAM MENILAI KINERJA KEUANGAN PADA PT. HANJAYA MANADALA SAMPOERNA, TBK - Mardahleni Mardahleni (Jurnal Apresiasi Ekonomi, 2017)
Financial evaluation is a very fundamental thing for a company, with a reasonable evaluation of the company's financial statements it will get information about the company's financial performance on a certain period. The purpose of this research is to know how financial performance of PTHanjaya mandala sampoernatbk, seen from profitability ratio analysis. The source of this research data is documentation in the form of financial statements consisting of balance sheet and income statement compiled by PT. Hanjaya Mandala Sampoerna TBK during 2012 until 2016. The method of analysis used in this study is a quantitative analysis of data analysis by performing a comparison of the results of financial ratio analysis (profitability ratios) for the period to be studied. The result of analysis shows that from the ratio of Gross Profit Margin (GPM) and Net Profit Margin (NPM) the company's financial performance is considered not good because the average rate is below the industry average. While from the analysis of return on equity (ROE) and return on investment (ROI) performance of the company is considered good because the average rate is above the industry average rate.